2006
DOI: 10.1093/ajcn/83.5.1062
|View full text |Cite
|
Sign up to set email alerts
|

Small organs with a high metabolic rate explain lower resting energy expenditure in African American than in white adults

Abstract: Racial differences in REE were reduced by >50% and were no longer significant when the mass of specific high-metabolic-rate organs was considered. Differences in FFM composition may be responsible for the reported REE differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 24 publications
(29 reference statements)
3
103
1
3
Order By: Relevance
“…The divergent results between studies completed in the United States and elsewhere have been attributed to differences in body composition and metabolic organ masses Hunter et al, 2004) in AAs. Recently, Gallagher et al (2006) found that after adjusting for differences in specific high-metabolic rate organs, differences in REE was no longer significantly different between AAs and Caucasians. While in the current study we were unable to adjust for smaller higher metabolic organ tissue, our results are similar because after adjusting for differences in FFM, differences in REE were no longer significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The divergent results between studies completed in the United States and elsewhere have been attributed to differences in body composition and metabolic organ masses Hunter et al, 2004) in AAs. Recently, Gallagher et al (2006) found that after adjusting for differences in specific high-metabolic rate organs, differences in REE was no longer significantly different between AAs and Caucasians. While in the current study we were unable to adjust for smaller higher metabolic organ tissue, our results are similar because after adjusting for differences in FFM, differences in REE were no longer significant.…”
Section: Discussionmentioning
confidence: 99%
“…While the Indian subjects weighed less had smaller fat mass and FFM and lower absolute REEs, these differences were no longer significant after adjusting for body composition differences. More recently, Gallagher et al (2006) attributed lower REE in AA than white adults to significantly smaller specific high metabolic rate organs (sum of liver, heart, spleen, kidneys and brain) in AA adults.…”
Section: Introductionmentioning
confidence: 99%
“…The implication, therefore, is that African Americans may have a significantly smaller proportion of FFM with high metabolic rate organs than do Whites, which helps explain many previous reports of lower REE adjusted for FFM in African Americans than in Whites. 37 In the study by Gallagher et al, 35 B50% of the observed remaining difference in REE between African American and White men and women, after adjusting for age, fat and FFM, could be explained by differences in the mass of these organs. Because REE is B65% of daily energy expenditure, the daily differences in REE observed in these studies (100-150 kcal), if not compensated for by a lower intake, may over a prolonged period of time be a contributing factor to the greater incidence of obesity in African-American than in White women.…”
Section: Weight Of Tissue (% Body Weight)mentioning
confidence: 94%
“…Over the past few years, the application of imaging techniques, such as computed tomography and magnetic resonance imaging, in quantification of the size of these tissues and organs in vivo has shown the potential of such an approach toward a better understanding of the contribution of these FFM subcomponents to the decline in REE with age 34 and in racial differences in REE. 35 It has been known for some time that, in comparison with White Americans, African Americans have significantly greater bone mass and skeletal muscle mass 36 and lower or similar FM 15 but a different fat distribution pattern. 15 Using magnetic resonance imaging, Gallagher et al 35 have extended this list of body composition differences to include lower masses of the liver, kidney, spleen, heart and brain.…”
Section: Weight Of Tissue (% Body Weight)mentioning
confidence: 99%
See 1 more Smart Citation